The landscape of COVID-19 clinical trials in Latin America and the Caribbean: assessment and challenges - Sarah Carracedo; Ana Palmero; Marcie Neil; Anisa Hasan-Granier; Carla Saenz; Ludovic Reveiz (Pan American Health Organization, 2020)
A considerable number of clinical trials is being conducted globally in response to the COVID-19 pandemic, including in low- and middle-income countries such as those in the Latin America and Caribbean region (LAC). Yet, an abundance of studies does not necessarily shorten the path to find safe and efficacious interventions for COVID-19. We analyze the trials for COVID-19 treatment and prevention that are registered from LAC countries in the International Clinical Trials Registry Platform, and identify a trend towards small repetitive non-rigorous studies that duplicate efforts and drain limited resources without producing meaningful conclusions on the safety and efficacy of the interventions being tested. We further assess the challenges to conducting scientifically sound and socially valuable research in the LAC region in order to inform recommendations to encourage clinical trials that are most likely to produce robust evidence during the pandemic.